No culture shock? Addressing the Achilles heel of modern Bible translations - S. J. Joubert (Acta Theologica)
Modern Bible translations are often more sensitive to the needs of their intended readers than to the right of biblical texts to be heard on their own terms as religious artefacts from the ancient Mediterranean world. Since all biblical documents linguistically embody socio-religious meanings derived from ancient Mediterranean societies, they also need to be experienced as different, even alien, by modern readers. Without an initial culture shock in encountering a Bible translation modern people are held prisoners by Western translations of the Bible. Therefore, translations should instil a new sensitivity among modern readers to the socio-cultural distance between them and the original contexts of the Bible. In order to help facilitate this historical awareness, a new  generation of “value added” translations must, in creative and responsible ways, begin to provide a minimum amount of cultural information to assist modern readers in assigning legitimate meanings to the linguistic signs encapsulated on the pages of the Bible.